Artificial intelligence in radiation therapy : first International Workshop, AIRT 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings /: first International Workshop, AIRT 2019, held in conjunction with MICCAI 2019, Shenzhen, China, October 17, 2019, Proceedings. (2019) - Unknown
No abstract available